2013
DOI: 10.2337/dc13-1031
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy and Microalbuminuria in Pregnant Women With Type 1 and Type 2 Diabetes

Abstract: OBJECTIVETo evaluate the prevalence of diabetic nephropathy and microalbuminuria in pregnant women with type 2 diabetes in comparison with type 1 diabetes and to describe pregnancy outcomes in these women following the same antihypertensive protocol.RESEARCH DESIGN AND METHODSAmong 220 women with type 2 diabetes and 445 women with type 1 diabetes giving birth from 2007–2012, 41 women had diabetic nephropathy (albumin-creatinine ratio ≥300 mg/g) or microalbuminuria (albumin-creatinine ratio 30–299 mg/g) in earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 38 publications
3
45
1
6
Order By: Relevance
“…This is in contrast to our previous observations in other type 1 diabetes patients [25] and the Finnish background population, in which every third parturient is currently overweight and 13% are obese [26]. The frequency of smoking during pregnancy was higher than the 15-17% recorded in 1987-2010 for all Finnish parturients [27], but similar to the figures reported by Damm et al [4]. There is a need to intensify the antismoking counselling given to reproductive-age women with diabetic nephropathy, as smoking may promote the development of diabetic renal disease [28].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is in contrast to our previous observations in other type 1 diabetes patients [25] and the Finnish background population, in which every third parturient is currently overweight and 13% are obese [26]. The frequency of smoking during pregnancy was higher than the 15-17% recorded in 1987-2010 for all Finnish parturients [27], but similar to the figures reported by Damm et al [4]. There is a need to intensify the antismoking counselling given to reproductive-age women with diabetic nephropathy, as smoking may promote the development of diabetic renal disease [28].…”
Section: Discussionsupporting
confidence: 69%
“…Diabetic nephropathy, which complicates 2.5-5% of type 1 diabetes pregnancies [3,4], is associated with a particularly high risk of hypertensive disorders of pregnancy, preterm birth, intrauterine growth restriction and perinatal mortality [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment goal was a blood pressure below 135/85 mmHg and urinary albumin excretion below 300 mg/24 h. If the woman was receiving antihypertensive treatment prior to pregnancy, the treatment was shifted to pregnancy-friendly drugs such as methyldopa without interruption in antihypertensive treatment. In our most recent publication, average blood pressure in both early and late pregnancy were approximately 128/70 mmHg, both in women with microalbuminuria and in those with diabetic nephropathy, and only one out of 41 women with kidney involvement developed nephrotic proteinuria [7]. The study also included women with type 2 diabetes, and women with kidney involvement showed similar pregnancy outcomes, regardless of type of diabetes.…”
mentioning
confidence: 99%
“…Our group in Copenhagen has published data on several small population-based series of pregnant women with kidney involvement (such as microalbuminuria or diabetic nephropathy) who were given early and intensive antihypertensive treatment, mainly methyldopa and labetalol, for blood pressure reduction [5][6][7]. The treatment goal was a blood pressure below 135/85 mmHg and urinary albumin excretion below 300 mg/24 h. If the woman was receiving antihypertensive treatment prior to pregnancy, the treatment was shifted to pregnancy-friendly drugs such as methyldopa without interruption in antihypertensive treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation